In situ synthesized Au–Ag nanocages on graphene oxide nanosheets: a highly active and recyclable catalyst for the reduction of 4-nitrophenol. (21st December 2015) - Hong, Min; Xu, Lidan; Wang, Fangli; Xu, Shuling; Li, Haibo; Li, Chen-zhong; Liu, Jifeng
Abstract : Graphene oxide-supported hollow Au–Ag alloy nanocages were synthesized here, which exhibited short induction time, high catalytic activity and good stability against agglomeration for the reduction of 4-nitrophenol to 4-aminophenol. Abstract : Graphene oxide-supported hollow Au–Ag alloy nanocages (AuAgNC/GO) with tunable shell composition were in situ fabricated by employing a galvanic replacement reaction (GRR) between HAuCl4 and Ag nanoparticles loaded on graphene oxide nanosheets (AgNP/GO). AgNPs on the graphene oxide nanosheets were first synthesized as sacrificial templates by the microwave method. The as-synthesized hybrid materials were characterized by TEM, EDX, HAADF-STEM, XRD and XPS. On the well-known 4-nitrophenol (4-NP) reduction to 4-aminophenol (4-AP) in the presence of excess borohydride, AuAgNC/GO as a solid phase heterogeneous catalyst has been investigated, which exhibited a short induction time, high catalytic activity and good stability against agglomeration for the reduction.